A Novel Standalone Human Waste Management System in Railway Station for Converting Faeces into Electricity - Rajasekaran R.,; Gokulalakshmi A.,; Abirami G., (Journal of Electronic Design Engineering, 2020)
In these days and age human waste management in railway track plays a major role in day today scenario. This paper introduces an effective waste management system to keep the railway station clean. It was found that the tracks are littered with human waste, food packets, bags and plastic water bottles. At present the human excreta are disposed by means of manual scavenging. People engaged in this activity are the worst victims of untouchability. They are considered untidy and impure; they are placed at the lowest level of the caste hierarchy. In order to avoid all these, a waste management unit are to be designed that should automatically dispose the human waste and alternatively it renovates the waste in to electricity. The deliberate waste management unit consists of storage chamber for storing the waste, trolley with wheel to budge over the rail track, suction blower for sucking all types of waste present in the track and water tank for storing water and consequently it cleans the railway track.